2022
DOI: 10.1038/s41467-022-32994-7
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance genetically encoded fluorescent indicator for in vivo cAMP imaging

Abstract: AbstractcAMP is a key second messenger that regulates diverse cellular functions including neural plasticity. However, the spatiotemporal dynamics of intracellular cAMP in intact organisms are largely unknown due to low sensitivity and/or brightness of current genetically encoded fluorescent cAMP indicators. Here, we report the development of the new circularly permuted GFP (cpGFP)-based cAMP indicator G-Flamp1, which exhibits a large fluorescence increase (a maximum ΔF/F0 of 1100% in HEK293T cells), decent br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 76 publications
4
47
0
Order By: Relevance
“…For dual-color imaging, we employed different excitation wavelengths: 560 nm for RCaMP3 imaging and 405 nm and 470 nm for cAMPinG1 ratiometric imaging. In line with previous studies (Massengill et al, 2022; Wang et al, 2022), we observed an increase in cAMP levels during the running period following the increase in Ca 2+ levels ( Figures 6B-6D ). Surprisingly, cAMP levels decreased after the running period and remained low for tens of seconds.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…For dual-color imaging, we employed different excitation wavelengths: 560 nm for RCaMP3 imaging and 405 nm and 470 nm for cAMPinG1 ratiometric imaging. In line with previous studies (Massengill et al, 2022; Wang et al, 2022), we observed an increase in cAMP levels during the running period following the increase in Ca 2+ levels ( Figures 6B-6D ). Surprisingly, cAMP levels decreased after the running period and remained low for tens of seconds.…”
Section: Resultssupporting
confidence: 93%
“…The green fluorescence intensity of cAMPinG1 increased by 1,000 % upon binding to cAMP with blue light (488 nm), while the green fluorescence intensity decreased by 61 % with violet light (405 nm), resulting in a 2,700 % ratio change with a combination of blue and violet excitation in HEK293T cell lysate. The large ratio change dependent on the decrease of fluorescence intensity with violet excitation indicates that cAMPinG1 is suitable for ratiometric imaging, in contrast to some cpGFP-type indicators such as GCaMPs and G-Flamp1, which do not show a fluorescence decrease with violet excitation (Inoue et al, 2019; Wang et al, 2022) ( Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations